Rare earth metals and minerals industries : status and prospects - Murty, Yellapu V.; Alvin, Mary Anne; Lifton, Jack P. (Springer, 2024)
This book presents the current status and future prospects of rare earth elements with respect to a multitude of factors, including resource availability, production, and applications. Among the topics covered are the extraction of raw materials, alloying and compound production, applications, resource conservation through recycling, regulatory issues, and potential new resource streams. The chapters are authored by well-known technical experts in their fields, with decades of research, industrial, and governmental policy experience. The book is expected to serve as the first single source reference on rare earth minerals and metals aimed at students, scientists, technologists, government legislators, regulatory agencies, investors, and business leaders. It provides in-depth examination of the importance of rare earth elements to the global economy and their use in technological innovation, including energy, power, transportation, medicine, electronics, and chemical/petroleum industries. Provides a comprehensive review of the current status and future prospects of Rare Earth Elements and their applications; Addresses critical socioeconomic issues surrounding these important materials; Examines a multitude of topics including resource conservation through recycling and potential new resource streams. .